2004
DOI: 10.1046/j.1399-0012.2003.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

The unrecognized posterior gastric artery: a potential cause of surgical complications in pancreas transplantation

Abstract: The relevance of the posterior gastric artery with regard to general surgical procedures was only recently recognized. Our case demonstrates that the posterior gastric artery is also important in transplant surgery. Awareness of this anatomical structure during organ procurement would help minimize pre-transplant vascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Overlooking the PGA during pancreas harvesting can lead to significant bleeding and its treatment to damage the vascular supply and loss of the graft. Troppman et al reported a case where overlooking the PGA lead to a splenic artery injury during procurement (Troppmann et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Overlooking the PGA during pancreas harvesting can lead to significant bleeding and its treatment to damage the vascular supply and loss of the graft. Troppman et al reported a case where overlooking the PGA lead to a splenic artery injury during procurement (Troppmann et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Unusual branching pattern of SA to distal one third of the transverse colon has been reported [11]. This atypical pattern of distribution of SA is vulnerable to bleed profusely during abdominal operations when they are overlooked [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although investigated and depicted in many anatomical studies, a consensus regarding the incidence, course and distribution of PGA is not yet reached 4 . Many variations in the course and branching patterns of splenic artery are mentioned in the literature [5][6][7][8][9] . However, a branch of the splenic artery to colon is rare 10,11 .…”
Section: Introductionmentioning
confidence: 99%